Advances of capillary electrophoresis enantioseparations in pharmaceutical analysis (2017–2020). Issue 17 (22nd January 2021) - Krait, Sulaiman; Konjaria, Mari‐Luiza; Scriba, Gerhard K. E.
Abstract: Capillary electrophoresis is a powerful technique for the analysis of polar chiral compounds and has been widely accepted for analytical enantioseparations of drug compounds in pharmaceuticals and biological media. In addition, many mechanistic studies have been conducted in an attempt to rationalize enantioseparations in combination with spectroscopic and computational techniques. The present review will focus on recent examples of mechanistic aspects and summarize recent applications of stereoselective pharmaceutical and biomedical analysis published between January 2017 and November 2020. Various separation modes including electrokinetic chromatography in combination with several detection modes including laser‐induced fluorescence, mass spectrometry and contactless conductivity detection will be discussed. A general trend also observed in other analytical techniques is the application of quality by design principles in method development and optimization.